Household Characteristics and Nutritional Status of Children to Children in Coastal Family in Bengkulu Province - Emy Yuliantini; Ketut Sukiyono; Bambang Sulistyo; M. Zulkarnain Yuliarso (Media Gizi Indonesia, 2023)
Coastal areas have a lot of natural wealth potential. The poor nutritional status of children under five in fishing families is greater than in farming families. Family characteristics such as education, knowledge, work and family income are the most important parts in ensuring family food security, so it is necessary to know the characteristics and nutritional status of children under five in coastal families in Bengkulu province. The research method is descriptive analytic with a cross-sectional approach. The sample in this study were mothers who had children under five in the locus and not loci stunting on the coast of Bengkulu province totaling 479. The result of the research is that most of the characteristics of children under five are < 3 years old. Gender is mostly female. Mother's Characteristics Factors are mostly <35 years old, while most of them have high education. Almost all mothers of toddlers do not work. Meanwhile, the majority of family incomes are still below the minimum wage. Of the three indicators of BB/U, TB/U, and BB/TB Bengkulu coastal families have public health problems. The food security factor of food diversity is mostly food security, the analysis of the quantity of food in the medium category and the analysis of the highest food quality are utilized. It is hoped that the characteristics and risk factors for the occurrence of community nutritional problems in children under five in coastal areas are a concern and need further researchers with different research methods.